Nilai Moral dalam Nazham Al-Imrithi untuk Penguatan Pendidikan Karakter Santri di Pesantren - Toha Harun Al Rasid; Ahmad Faozi (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aims to identify the moral values contained in Manzhumah Ad-Durrah Al-Bahiyyah, also known as Nazham Al-Imrithi, by Shaykh Sharafuddin Al-Imrithi. He was a scholar who often embedded moral values in his work, Nazham Al-Imrithi. This practice reflects one of the scholarly traditions of Muslim ulama, namely transmitting moral teachings through poetry from one generation to another. These moral teachings can serve as a foundation for character education in pesantren. Methods – This study employed library research. The primary source of this study was Manzhumah Ad-Durrah Al-Bahiyyah. The secondary sources consisted of commentary texts that explain the works of Shaykh Sharafuddin Al-Imrithi. The researcher also used the works of KH Hasyim Asy’ari and Shaykh Burhanuddin Az-Zarnuji to verify the moral values identified in relation to the ethical traditions of santri taught in pesantren. Findings – This study found that Manzhumah Ad-Durrah Al-Bahiyyah by Shaykh Sharafuddin Al-Imrithi contains several moral values that can strengthen character education in pesantren. These moral values include the etiquette of santri in the learning process, etiquette in relation to Allah, and etiquette in relation to society. The etiquette of santri indicates that during the learning process, manners and ethics must be maintained both in relationships with fellow human beings and, more importantly, in one’s relationship with Allah.Research Implications – This study is expected to provide an overview of the moral values contained in Manzhumah Ad-Durrah Al-Bahiyyah by Shaykh Sharafuddin Al-Imrithi. The findings seek to contribute knowledge about moral values that can strengthen character education in pesantren.